Semantic cognition: a cognitive neuroscience approach - Lambon-Ralph, Matthew (Henry Stewart Talks, 2010)
Semantic cognition, The combination of semantic memory, concepts and semantic control to generate semantically-driven behavior and comprehension, Semantic dementia, Multimodal semantic impairment in stroke aphasia, Functional neuroimaging of semantic processes and repetitive transcranial magnetic stimulation, Multi-method cognitive neuroscience research